偏光MPLを用いたニーオルスン上空の氷雲出現の雲底温度依存性に関する解析 - 山田, 恭平 (2017)
雲を構成する水・氷粒子は大気中の水蒸気量の1%以下に過ぎないが、地表面での放射収支に影響を与える要素である。雲相の情報は雲の微物理特性に直結するため重要であるが、北極域では低温乾燥や高いアルベドによって観測が難しく、その知識は十分ではない。国立極地研究所によって2013年にニーオルスンに設置された偏光マイクロパルスライダー（PMPL）は、高精度・高解像度でエアロゾルや雲の鉛直分布の観測を行い、後方散乱光の偏光情報を用いることで粒子の形状情報を得ることができる観測機器である。本研究ではこのニーオルスンのPMPLを用い、地上ライダーが特に得意とする雲底に関して、相判別とその温度依存性の解析を行った。雲底に氷を含む割合は雲底温度に対してほぼ一次相関の関係にあった。氷雲の出現頻度については他地域で同様の解析が行われており、この解析結果と本研究での結果はよく一致した。 Cloud is constructed only below 1 % of atmospheric water but one of the important factors to affect on the surface radiation budget. Cloud phase affects on the microphysics, however the knowledge in the Arctic region is limited because of dry atmosphere and high surface. Polarized micro-pulse lidar (PMPL) at Ny-Alesund, Svalbard (78˚56’N, 11˚52’, 40m a.s.l.) installed by the National Institute of Polar Research (NIPR) in 2013 has capability of high-accuracy and -resolution observation of vertical distributions of aerosol and cloud. PMPL also retrieves the particle-shape information by depolarization of the backscatter. This study analyzed phase of cloud base and the dependency on temperature with observation data of PMPL. Ratio of ice-containing cloud at base altitude shows the linear relationship with cloud base temperature. In comparison with the previous study about the frequency appearance of ice cloud in the other regions, the results correspond to the present study. Polar Meteorology and Glaciology Group seminar / 気水圏コロキウム 日時：3月8日（水）10:00-10:50 場所：C301（3階セミナー室） conference object